2020
DOI: 10.21595/mme.2019.21229
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency vibration analysis of heavy vehicle suspension system under various operating conditions

Abstract: To evaluate the acceleration-frequency characteristics of the suspension system of the heavy vehicles, a nonlinear dynamic model of two-axle heavy vehicles is established. A calculation method based on the complex domain is applied to solve the vibration equations of the heavy vehicle in the frequency domain instead of the traditional time domain. Matlab software is then used to calculate the vibration equations under various operating conditions. The research results show that the resonant frequency of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The vibration can be caused by the mechanical resonance of the ELF. Previous studies have reported that trucks exhibit mechanical resonance in the low-frequency range owing to their heavy mass and low rigidity (Hassan and McManus, 2002; Koayashi, 2012; Ramakrishnan and Pecht, 2004; Vanliem et al, 2020). Vibration negatively impacts yaw-rate control and the risk of cargo damage.…”
Section: Experimental Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The vibration can be caused by the mechanical resonance of the ELF. Previous studies have reported that trucks exhibit mechanical resonance in the low-frequency range owing to their heavy mass and low rigidity (Hassan and McManus, 2002; Koayashi, 2012; Ramakrishnan and Pecht, 2004; Vanliem et al, 2020). Vibration negatively impacts yaw-rate control and the risk of cargo damage.…”
Section: Experimental Systemmentioning
confidence: 99%
“…The natural frequency of the vibration mode in a truck tends to be lower because of its mass and low rigidity (Soleimani and Ahmadi, 2014). In particular, large vibrations are known to occur at 1–3 Hz due to the unevenness of the road surface during the lateral control of the truck (Hassan and McManus, 2002; Koayashi, 2012; Ramakrishnan and Pecht, 2004; Vanliem et al, 2020). The control system can lose steering control through vibrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main means of freight transportation, scholars have done a lot of research to improve the performance of heavy vehicles, [1][2][3][4][5] especially the road damage 6,7 caused by heavy vehicles. In order to improve the ride comfort and road friendliness of heavy vehicles, Gong and Yan Mingde 8 proposed a new adaptive robust control strategy based on road level estimation for heavy rescue vehicles to improve ride comfort and handing stability.…”
Section: Introductionmentioning
confidence: 99%